PENGARUH JENIS MEDIA PENDINGIN TERHADAP GETARAN DAN NILAI KEKASARAN PERMUKAAN PADA PEMBUBUTAN MATERIAL BAJA AISI 1045 - Mudjijanto Mudjijanto; Hendri Destriyanto; Ali Achmadi; Sarjono Sarjono (Universitas Muria Kudus, 2024)
The coolant in the turning process functions to stabilize the temperature in the cutting process in addition to the temperature on the workpiece as well as the temperature on the tool, where an increase in temperature will certainly cause changes in mechanical properties. This research aims to find a correlation between surface roughness and vibration with variations in cooling in the AISI 1045 steel turning process. The research method for the AISI 1045 steel turning process is with a depth of cut 1 mm and a feed rate of 0.21 mm/rev and a rotation of 1,160 rpm, cooling using with variations, without cooling, dromus, and air coolant. Vibrations are detected in the tool during the turning process using a vibration meter and the surface roughness results are measured using a surface roughnees tester. The results show that the highest vibration value was produced in the process without cooling at 4.8 mm/s2, then the coolant cooler produced a vibration value of 4.3 mm/s2, and the dromus cooler produced the lowest vibration value at 3.9 mm/s2. Meanwhile, the highest surface roughness value was produced in the turning process without cooling at 6.247 µm, then the coolant cooling media produced a surface roughness value of 5.442 µm, and the dromus cooler produced the lowest surface roughness value at 4.848 µm. The vibration value and surface roughness show that there is a correlation that the higher the vibration, the higher the surface roughness value produced by turning AISI 1045 steel.